Low-intensity pulsed ultrasound promotes periodontal regeneration in a beagle model of furcation involvement - Wang, Yue; Xiao, Qingyue; Zhong, Wenjie; Zhang, Chuangwei; Yin, Yuanyuan; Gao, Xiang; Song, Jinlin (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: To evaluate the regeneration potential of periodontitis tissue treated by low-intensity pulsed ultrasound (LIPUS) combined with guided tissue regeneration (GTR) technique in a beagle model of furcation involvement (FI). Background: Achieving predictable regeneration remains a clinical challenge for periodontitis tissue due to the compromised regenerative potential caused by chronic inflammation stimulation. LIPUS, an FDA-approved therapy for long bone fracture and non-unions, has been demonstrated effective on the in vitro attenuation of inflammation-induced dysfunction of periodontal ligament stem cells (PDLSCs), the key cells contributing to periodontal regeneration. However, the in vivo effect of LIPUS on periodontitis tissue is rarely reported. Methods: A beagle model of FI was established, and the experimental teeth were randomly assigned into three groups: control group, GTR group, GTR+LIPUS group. Radiographic examinations were performed, and clinical periodontal parameters were recorded to reflect the periodontal condition of different groups. Histological analyses using H&E and Masson’s staining were conducted to evaluate the periodontal tissue regeneration. Results: LIPUS could enhance new periodontal bone formation and bone matrix maturity in FI after GTR treatment. Moreover, clinical assessment and histomorphometric analyses revealed less inflammatory infiltration and superior vascularization within bone grafts in the LIPUS treatment group, indicating the anti-inflammation and pro-angiogenesis effect of LIPUS in FI. Conclusions: Our investigation in a large animal model demonstrated that LIPUS is a promising adjunctive approach for regeneration of periodontitis tissue, paving a new avenue for LIPUS application in the field of periodontal regenerative medicine.